Plasmodium infection, anaemia and mosquito net use among school children across different settings in Kenya - Gitonga, C; Edwards, T; Karanja, P; Noor, A; Snow, R; Brooker, S (2012)
Objective To investigate risk factors, including reported net use, for Plasmodium infection and anaemia among school children and to explore variations in effects across different malaria ecologies occurring in Kenya. Methods This study analysed data for 49975 school children in 480 schools surveyed during a national school malaria survey, 2008-2010. Mixed effects logistic regression was used to investigate factors associated with Plasmodium infection and anaemia within different malaria transmission zones. Results Insecticide-treated net (ITN) use was associated with reduction in the odds of Plasmodium infection in coastal and western highlands epidemic zones and among boys in the lakeside high transmission zone. Other risk factors for Plasmodium infection and for anaemia also varied by zone. Plasmodium infection was negatively associated with increasing socio-economic status in all transmission settings, except in the semi-arid north-east zone. Plasmodium infection was a risk factor for anaemia in lakeside high transmission, western highlands epidemic and central low-risk zones, whereas ITN use was only associated with lower levels of anaemia in coastal and central zones and among boys in the lakeside high transmission zone. Conclusions The risk factors for Plasmodium infection and anaemia, including the protective associations with ITN use, vary according to malaria transmission settings in Kenya, and future efforts to control malaria and anaemia should take into account such heterogeneities among school children. © 2012 Blackwell Publishing Ltd.